Preferential pattern of mouse neutrophil cell death in response to various stimulants - Nuttira Luehong (2018)
© 2017, The Society for In Vitro Biology. Neutrophils undergo cell death processes once their physiological function has been fulfilled. Apoptosis, necrosis, pyroptosis, or NETosis, a unique form of cell death, could occur, depending on the type of stimulant or inhibitory intervention. We investigated whether phorbol myristate acetate (PMA) and Klebsiella pneumoniae (KP), serving as stimulants, or whether an inhibitor (cytochalasin B, CytB) could alter the morphology and gene expression pattern associated with mouse neutrophil cell death. Fluorescence microscopy, flow cytometry, and real-time PCR approaches were used to identify morphological changes, percentages of cell death, and gene expression patterns, respectively. The results showed an increase in the percentage of cell death in PMA and KP groups, whereas CytB exerted inhibitory effects. Fluorescently stained cell nuclei revealed significantly different percentages of cell death among treatments. Moreover, there was a stepwise increase in cell death from 90 to 150 min after stimulation. Quantification of the release of neutrophil extracellular traps (NETs) demonstrated clearly elevated amounts in cells stimulated with KP, while the amount of NETs was slightly increased or unchanged with PMA or CytB treatments. Analysis of the genes involved in cell death revealed that mRNA expression of CASP1, IL1β, IL18, MCL1, NLRP3, and PYCARD was down-regulated in the PMA group, with the exception of AIM2 and CASP3. The expression of AIM2, IL1β, MCL1, and NLRP3 was up-regulated in KP-stimulated neutrophils, while CASP1, CASP3, IL18, and PYCARD genes were down-regulated. In summary, a spectrum of specific cell stimulants and exposure durations accounted for different outcomes in mouse neutrophil cell death.